PHYTOREMEDIATION OF SOIL CONTAMINATION WITH SOME HEAVY METALS (NI, CD, PB) USING OLEANDER PLANT.: PHYTOREMEDIATION OF SOIL CONTAMINATION WITH SOME HEAVY METALS (NI, CD, PB) USING OLEANDER PLANT. (Iraqi Journal of Market Research and Consumer Protection, 2026)
A biological experiment was conducted according to a completely randomized design (CRD) in woody canopy using phytoremediation technology to reclaim soils polluted with some heavy metals (Ni, Cd, Pb) biologically by planting Oleander plant. Based on calculation of global environmental pollution indicators, with three factors and six replicates, namely soil contamination with three heavy elements: Pb, Cd, and Ni, and four combinations: Pb + Cd, Cd + Ni, Ni + Pb, and Pb + Ni + Cd. with two element levels: 0 and 120 for Lead, 0 and 10 for Cadmium, and 0 and 70 mg kg-1 for Nickel, using Loamy Sand soil. The coefficients were coded as follows: N, C, P, CN, NP, CP, CNP, and O. Results showed an increase in values of Bio concentration factor (BCF) of root system of  Oleander plant for Nickel for treatments N, CN, CNP, and PN treatments reaching 22.93, 19.87, 18.16, and 17.78, respectively, and it decreased in rest of treatments. Highest values for Cadmium were in C, then CN, CP, and CNP treatment, reaching 3.20, 2.65, 2.37, and 2.18. Thus, Oleander plant is considered one of plants that accumulate Cd. BCF was low for Pb, values of BAC increased with increasing concentrations of available heavy metals in soil. Values of TF for Cd, Ni, and Pb are lower than value of one.